A Review on the Role of Microbes in Polyethene Degradation - Okoth , Beryle Atieno; Makonde, Huxley Makonde; Bosire, Carren; Jeophita, June Mwajuma; Kibiti, Cromwell Mwiti (Multidisciplinary Journal of Technical University of Mombasa, 2023)
Polyethene is a polyolefin produced from polymerization of the olefin ethylene (C2H4). It is one of the most commonly used plastic and one of the most resistant to degradation. Its accumulation in the surrounding has caught the attention of many governments and researchers with attempts to come up with better disposal methods. This review focused on the role played by microorganisms in the degradation of polyethene. The references reviewed were obtained from journals and databases including PubMed, Google Scholar (http: //scholar. google.com) and Science Direct (http://www.science direct.com). We focused on data published from 2010 up to 2021. The findings obtained indicated that 19 genera of bacteria and actinomycetes and 5 fungal genera have the ability to degrade polyethene through secretion of extracellular depolymerases. The enzymes cleave polymer chains into low molecular weight fragments, which are then assimilated through the microbial cell membrane and mineralized. Microbial degradation is a sustainable and promising idea. However, there is need for more research to clearly determine the mechanism of enzymatic degradation, which will be useful in the development of novel biotechnological tools for degradation of a variety of plastic materials by microorganisms.
Keywords: Degradation, Microorganisms.; Polyethene, Depolymerases